2020
DOI: 10.5114/ceji.2020.97907
|View full text |Cite
|
Sign up to set email alerts
|

Study of selective immunoglobulin A deficiency among Egyptian patients with food allergy

Abstract: Introduction: iga deficiency is one of the commonest primary antibody deficiencies. although many affected individuals could be asymptomatic, selected patients suffer from recurrent mucosal infections, allergies, and autoimmune diseases.Aim of the study: to investigate the prevalence of iga deficiency among egyptian patients with food allergy.Material and methods: we studied 100 patients (62 males, 38 females; mean age, 28.6 years) with multiple food allergies who were recruited on the basis of adequate immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…However, their study was conducted on a population different from the population of the present study as they investigated the prevalence of IgA deficiency among Egyptian patients with food allergy. 24 Nonetheless, Kim et al disagreed with the current results regarding the correlation between serum IgA and serum IgE and age. They declared that serum IgE level was positively related to serum IgA level.…”
Section: Dovepresscontrasting
confidence: 59%
“…However, their study was conducted on a population different from the population of the present study as they investigated the prevalence of IgA deficiency among Egyptian patients with food allergy. 24 Nonetheless, Kim et al disagreed with the current results regarding the correlation between serum IgA and serum IgE and age. They declared that serum IgE level was positively related to serum IgA level.…”
Section: Dovepresscontrasting
confidence: 59%
“…Shahin et al have also reached a similar conclusion. They have revealed serum IgA level is correlated with serum IgE level, and the correlation is significantly negative [ 65 ]. Several studies have confirmed that serum IgE levels of asthmatic patients are elevated [ 66 , 67 ].…”
Section: The Relationship Between Siga and Pulmonary Diseasesmentioning
confidence: 99%
“…The results from both of these studies suggest that a diminished humoral immune response enhances sensitivity to gluten. This is not without precedent, as humoral immunodeficiency has previously been shown to enhance immune responses to other dietary antigens in both mouse models [31][32][33] as well as humans [34][35][36][37]. From these observations we sought to determine how exposure to a gluten-free diet influences the microbiota and report several interesting findings.…”
Section: Discussionmentioning
confidence: 99%